Correlation of Prostate-Imaging Reporting and Data Scoring System scoring on multiparametric prostate magnetic resonance imaging with histopathological factors in radical prostatectomy material in Turkish prostate cancer patients: a multicenter study of the Urooncology Association - Fuat Kızılay; Serdar Çelik; Sinan Sözen; Bora Özveren; Saadettin Eskiçorapçı; Mahir Özgen; Haluk Özen; Bülent Akdoğan; Güven Aslan; Fehmi Narter; Çağ Çal; Levent Türkeri (Prostate International, 2020)
Background: Histopathological features after radical prostatectomy (RP) provide important information for the prognosis of prostate cancer (PCa). The possible correlations between Prostate-Imaging Reporting and Data Scoring System (PIRADS) scores in multiparametric magnetic resonance imaging (mpMRI) may also be predictive for prognosis. In this study, we aimed to evaluate the correlation of PIRADS scores with histopathological data. Methods: A total of 177 patients who underwent preoperative mpMRI and RP for PCa from eight institutions were included in the study. Correlation of PIRADS score in preoperative mpMRI with adverse histopathological factors in RP specimen was investigated using univariate and multivariate analyses. Results: The relationship between PIRADS score and postoperative extracapsular extension, lymphovascular invasion, and seminal vesicle involvement was significant (P < 0.001, P = 0.032, and P = 0.007, respectively). Although the PIRADS score was significantly correlated with the number of dissected lymph nodes (p = 0.026), it had no significant correlation with the number of positive nodes (P = 0.611). Total Gleason score, extracapsular extension, seminal vesicle invasion, and number of lymph nodes were found to be independent factors, which correlated with high PIRADS scores in ordinal logistic regression analysis. Conclusion: PIRADS scoring system in mpMRI showed a statistically significant correlation with adverse histopathological factors in RP specimen. A higher PIRADS score may help to predict a higher Gleason score, indicating clinically important PCa as well as poor prognotic factors such as extracapsular extension, lymphovascular invasion, and seminal vesicle invasion that may indicate a higher risk of recurrence and the need for additional treatment. Keywords: Histopathology, Multiparametric magnetic resonance imaging prostate, PIRADS, Prostate neoplasms